Serwis internetowy w działalności promocyjnej obiektów hotelarskich Dolnego Śląska - Rapacz, Andrzej; Michalska-Dudek, Izabela (Using Web Page in the Functioning of Hotels in Lower Silesia Region, 2008)
Among information technologies applied in tourist sector, the Internet has been occupying the most important role and has become in recent years the platform for the development of diversified type of reservations and sales applications. The hereby article presents opportunities for the application of modem information technologies by tourist establishments as the tool of their promotional policy. Most frequently this medium is used for the presentation of a tourist enterprise offer, which is supposed to result in booking and sales of tourist services. The article also presents surveys results referring to the degree and scope of the Internet application in promotional activities related to hotels functioning in Lower Silesia region. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 29, s. 146-159